ABORTION OR HOMICIDE: BIRTH AS A DIFFERENTIATING CRITERION AND THE QUESTIONABLE INTERPRETATION OF CRIMINAL JURISPRUDENCE, IN THE LIGHT OF THE RULE OF LAW - Ugalde González, Olman Francisco (2022)
In this text, it is intended to address the legitimacy of the differentiated treatment between abortion and homicide, to examine the legal rights protected by each of these figures, as well as to clarify from what moment and until when each one is protected. In this sense, it is carried out, on one hand, an approach based on the particularities of the Costa Rican regulations and from the principle of legality and restrictive interpretation; while, on the other hand, the criteria followed by the courts and the existing problems.